Consecuencias del distanciamiento social a causa de la Covid-19 en el empleo y el mercado laboral peruano: Estadísticas y retos jurídico-normativos - Egúsquiza Palacín, Betty (2023)
The Peruvian labor market was hit hard in 2020, the most critical year of the pandemic due to Covid-19. Although it seems that everything has recovered in 2021, in reality, the structural problems have been accentuated: greater informality of employment, increased predominance of fixed-term contracts and specific labor schemes, such as outsourced work and teleworking, which raise assumptions that in the new post-Covid context had not been discussed. On this occasion, we will focus on the employment and labor situation in the country in the pe-riod 2012-2021, showing that the state of affairs was already worrying and that the pandemic only aggravated the problem of the high informality of employment and the widespread use of fixed-term labor contracting, at the same time it opened the horizon of teleworking and once again brings to debate labor outsourcing, identifying some normative gaps that could constitute a whole development for a better and efficient labor regulation and institutionalism, besides calling attention to the urgent need for economic and active employment policies to overcome this reality.